Virtual prototyping applied to simulation with CAE software: aluminum alloy piston with ceramic material coating - Zardo, Alexandre Santos; Carvalho, Flavio Lucio Santos de (Brazilian Journal of Production Engineering, 2021)
Innovation in materials is an area that aims to generate improvements in existing products through activities with R&D. The automotive sector is one of the areas where investment is sought for better materials. Product engineering combined with virtual simulation, prototyping allows projects to be more assertive, with a reduction in planning progress, and the costs involved. The use of ceramic materials in internal combustion engines is still necessary for large-scale research, especially because of their sintering particularities and improved mechanical characteristics at extreme temperatures. The present research has the objective of proposing an optimization in an internal combustion engine by cycle of Otto cycle by replacing metal alloy material in the piston by Metallic Matrix Composite (CMM). For support in the disciplines of Material Science, Product Engineering and Simulation for the realization of the project, use of Inventor® and Ansys® software to validate a proposal of the idealized piston prototype, Aluminum alloy piston exchange fused with Ceramic Dioxide Silicon. The results obtained were a reduction in heat conduction as a function of time, the best mechanical attributes used and a reduction in the costs applied in the process of using ceramic motors in automotive engines.
Keywords: Piston. Coating. Silicon Dioxide. Ansys